1973
DOI: 10.1128/jb.113.3.1289-1295.1973
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Synthesis During the Germination of Saccharomyces cerevisiae Spores

Abstract: After the dormancy of Saccharomyces cerevisiae ascospores had been broken, the synthesis of proteins was observed first, followed rapidly by synthesis of ribonucleic acid (RNA) and much later by deoxyribonucleic acid (DNA) synthesis. Phosphoglucomutase activity increased in a periodic (step) fashion, whereas the activity of five other enzymes increased linearly during germination and outgrowth. The rate of synthesis of these enzymes was highest at about the period of DNA replication. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…What controls exist to prevent protein synthesis from occurring until germination is an open question. Our data, as well as the data of others (3,7,11,12,14,15,16,18,19,28,29,30,35), would argue that regulation must be at least partially at the level of translation. The observation that there is considerable poly(A)(+) RNA in yeast ascospores and that some of it is associated with polyribosomes suggests a number of molecular approaches to questions of maternal effects and to the persistence of information in RNA throughout the processes of meiosis and sporulation.…”
Section: J Bacteriolsupporting
confidence: 81%
See 1 more Smart Citation
“…What controls exist to prevent protein synthesis from occurring until germination is an open question. Our data, as well as the data of others (3,7,11,12,14,15,16,18,19,28,29,30,35), would argue that regulation must be at least partially at the level of translation. The observation that there is considerable poly(A)(+) RNA in yeast ascospores and that some of it is associated with polyribosomes suggests a number of molecular approaches to questions of maternal effects and to the persistence of information in RNA throughout the processes of meiosis and sporulation.…”
Section: J Bacteriolsupporting
confidence: 81%
“…We conclude from these results that ascospore polyadenylated RNA contains a 5' terminal cap analogous to that of vegetative cells (32). DISCUSSION Rousseau and Halvorson reported that during germination and outgrowth of ascospores of Saccharomyces cerevisiae, protein synthesis was detectable before any RNA synthesis occurred (28). This observation implied that ascospores contained mRNA which was functional during germination.…”
Section: J Bacteriolmentioning
confidence: 89%
“…Separation of spores from nonsporulated cells. (23). Sporulated cultures were treated with thioglycolate buffer, washed, and incubated with 1% glusulase in 1% Tween-80.…”
Section: Methodsmentioning
confidence: 99%
“…We reasoned that if there were segregated expression of ribosomal cistrons of the progeny genomes at some time during sporulation, two of the spores from a heterozygotic diploid would be phenotypically resistant to cycloheximide and would germinate on cycloheximide-containing medium. On the other hand, if the gene products in spores were characteristic of the diploid mother cell, none of the spores should be able to germinate on medium containing the antibiotic, since protein synthesis is the first observable macromolecular event in germination (23).…”
mentioning
confidence: 99%
“…Of those investigations performed, few have approached the germination of S. cerevisiae ascospores from the standpoint of changes in protein synthesis. Rather, previous studies have focused upon those conditions which initiate the germination process as well as the accompanying changes in the appearance of the yeast ascospores after germination has begun [1][2][3][4]. Protein synthesis in sporulating yeast cells and in germinating yeast ascospores has been examined using two-dimensional gel electrophoretic analysis'in prior studies [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%